Importing Political Polarization? The Electoral Consequences of Rising Trade Exposure - Autor, David; Dorn, David; Hanson, Gordon; Majlesi, Kaveh (American Economic Review, 2020)
Has rising import competition contributed to the polarization of US politics? Analyzing multiple measures of political expression and results of congressional and presidential elections spanning the period 2000 through 2016, we find strong though not definitive evidence of an ideological realignment in trade-exposed local labor markets that commences prior to the divisive 2016 US presidential election. Exploiting the exogenous component of rising import competition by China, we find that trade exposed electoral districts simultaneously exhibit growing ideological polarization in some domains, meaning expanding support for both strong-left and strong-right views, and pure rightward shifts in others. Specifically, trade-impacted commuting zones or districts saw an increasing market share for the Fox News channel (a rightward shift), stronger ideological polarization in campaign contributions (a polarized shift), and a relative rise in the likelihood of electing a Republican to Congress (a rightward shift). Trade-exposed counties with an initial majority White population became more likely to elect a GOP conservative, while trade-exposed counties with an initial majority-minority population became more likely to elect a liberal Democrat, where in both sets of counties, these gains came at the expense of moderate Democrats (a polarized shift). In presidential elections, counties with greater trade exposure shifted toward the Republican candidate (a rightward shift). These results broadly support an emerging political economy literature that connects adverse economic shocks to sharp ideological realignments that cleave along racial and ethnic lines and induce discrete shifts in political preferences and economic policy. (JEL D72, F14, J15, L82, R23)